Las técnicas de aprendizaje cooperativo en la enseñanza del área de Lengua y Literatura en los estudiantes de sexto año de educación básica de la Escuela Manuel Isaac Encalada Zúñiga de la parroquia Buenavista del cantón Pasaje, periodo lectivo 2012-2013. - Illescas Vélez, Lérida Mariela (2013)
The present research work is based on the study of cooperative learning techniques, being a subject of transcendental importance since the strategic application of these learning will derive the development of meaningful learning.